Model Evaluasi Penilaian Ranah Afektif Siswa dalam Pembelajaran PAI di SMP Negeri Samarinda - Sunarmi, Sri (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
Islamic education is a compulsory subject in every educational institution. Students are expected do not only know theory of religion but they also understand, feel, and implement theory of religion. Therefore, evaluation instrument of affective domain for Islamic education subject need to be developed and taken care since there has not been any evaluation instrument yet which is particularly developed for Islamic education subject. So this research aim at developing evaluation instrument of affective domain for Islamic education subject that fulfill validity and reliability requirement. Population of research object is evaluation instrument of affective domain assessment and population of research subjects are Junior High School students in Samarinda. Sample of this research is taken by using stratified proportional random sampling technique. Referring to the instrument construction, the use of revised GBPP of Islamic education subject for Junior High School is considered as the correct option. Data collection was done by using questionnaire technique. Data was analyzed by using Iteman analysis technique to find out degree of validity and reliability. Data analysis result reveals Likert method questionnaire, from the test of construct validity shows cumulative variant value 90.4% or it can show 94% of theory construct which has been stated. Reliability coefficient obtained is 0.914 with 0.124 SEM value which indicate very good quality of affective domain instrument. The use of sentences in constructing Likert method instrument assisted respondents to respond the instrument well. In Likert method, constructing questionnaire takes long sentences so that the respondents feel tired to read those statements. Likert method require sequence of words to formulate a good and objective statement. The implementation is that in Islamic education subject require efforts to take the decision.